Dune Russet: A French-Fry Potato Cultivar with High Specific Gravity under High-Temperature Growing Conditions and Excellent Processing Quality after Long-Term Cold Storage - M. Isabel Vales; Douglas C. Scheuring; Jeffrey W. Koym; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Joshua R. Johnson; Caroline P. Gray; David G. Holm; Mohamad Chikh-Ali; Robert G. Wilson; Richard G. Novy; Jonathan L. Whitworth; et al. (American Journal of Potato Research, 2026)
Dune Russet (COTX08063-2Ru) is the first French fry russet potato cultivar released by the Texas A&M Potato Breeding Program. It derives from a cross made by the Colorado State University Potato Program between Premier Russet and A99073-1 and was subsequently selected and advanced by the Texas Program. Dune Russet has oblong potato tubers with light russet skin texture and white flesh. It is characterized by having excellent French fry quality and cold-induced sweetening resistance, producing light-colored fries directly from the field and even after several months (three to eight) in cold storage at 4.4 °C. Dune Russet is especially recommended for areas that experience high-temperature stress during the growing season, as it can retain high specific gravity near 1.090 and produce light French fries despite heat stress. Across multi-location trials, Dune Russet outperformed the reference cultivar, Russet Burbank, and other processing cultivars in French fry quality, while offering some field-based PVY tolerance and good agronomic performance, including competitive marketable yields and a high proportion of US No. 1 tubers.

Early Tuberization: A Heat Stress Escape Strategy in the Fresh Market Potato Variety Vanguard Russet - Amaka M. Ifeduba; Sanjeev Gautam; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Douglas C. Scheuring; Jeffrey W. Koym; M. Isabel Vales (American Journal of Potato Research, 2024)

Vanguard Russet: A Fresh Market Potato Cultivar with Medium-Early Maturity and Long Dormancy - M. I. Vales; D. C. Scheuring; J. W. Koym; D. G. Holm; S. Y. C. Essah; R. G. Wilson; J. K. Sidhu; R. G. Novy; J. L. Whitworth; J. C. Stark; R. R. Spear; V. Sathuvalli; et al. (American Journal of Potato Research, 2022)

Identification of Tetraploid Potato Clones with Good Processing Quality among Genotypes with Reduced Zebra Chip Disease Symptomatology - Samuel J. Vigue; Douglas C. Scheuring; Jeffrey W. Koym; Charles M. Rush; Fekede Workneh; Cecilia Tamborindeguy; J. Creighton Miller; David S. Douches; Richard G. Novy; M. Isabel Vales (American Journal of Potato Research, 2020)

Incorporation of Mannitol in Tissue Culture Media for Long-Term Storage of Potatoes at Moderately Low Temperature and Effect on Subsequent Micropropagation - Angel L. Chappell; Jeffrey W. Koym; Douglas C. Scheuring; J. Creighton Miller; M. Isabel Vales (American Journal of Potato Research, 2020)

Differences in Zebra Chip Severity between ‘Candidatus Liberibacter Solanacearum’ Haplotypes in Texas - Kyle Harrison; Cecilia Tamborindeguy; Douglas C. Scheuring; Azucena Mendoza Herrera; Adrian Silva; Ismael E. Badillo-Vargas; J. Creighton Miller; Julien G. Levy (American Journal of Potato Research, 2019)

Population structure analysis and association mapping for iron deficiency chlorosis in worldwide cowpea (Vigna unguiculata (L.) Walp) germplasm - Waltram Ravelombola; Jun Qin; Ainong Shi; J. Creighton Miller; Douglas C. Scheuring; Yuejin Weng; Gehendra Bhattarai; Lingdi Dong; Wei Yang (Euphytica, 2018)

Reveille Russet: An Early, Widely Adapted, High-Count-Carton Russet for the Fresh Market - J. C. Miller; D. C. Scheuring; J. W. Koym; D. G. Holm; J. J. Pavek; R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; et al. (American Journal of Potato Research, 2018)

The Use of Low-Dose Electron-Beam Irradiation and Storage Conditions for Sprout Control and their Effects on Xanthophylls, Antioxidant Capacity, and Phenolics in the Potato Cultivar Atlantic - Tyann Blessington; Douglas C. Scheuring; M. Ndambe Nzaramba; Anna L. Hale; Lavanya Reddivari; Tom A. Vestal; Joseph E. Maxim; J. Creighton Miller (American Journal of Potato Research, 2015)

ATTX961014-1R/Y a.k.a. Sierra RoseTM: A Red-Skin, Yellow-Flesh Potato Cultivar for the Specialty/Gourmet Market - J. C. Miller; D. C. Scheuring; J. W. Koym; D. G. Holm; J. J. Pavek; R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; et al. (American Journal of Potato Research, 2015)

Investigations on Putative Zebra Chip Tolerant Potato Selections - Julien G. Lévy; Douglas C. Scheuring; Jeffrey W. Koym; Don C. Henne; Cecilia Tamborindeguy; Elizabeth Pierson; J. Creighton Miller (American Journal of Potato Research, 2015)

Relationships Among Antioxidant Activity, Total Phenolic Content and Specific Gravity in Several Potato (Solanum tuberosum L.) Cultivars Grown in Different Environments - M. Ndambe Nzaramba; Douglas C. Scheuring; Jeffrey W. Koym; J. Creighton Miller (American Journal of Potato Research, 2013)

Cooking Methods and Storage Treatments of Potato: Effects on Carotenoids, Antioxidant Activity, and Phenolics - Tyann Blessington; M. Ndambe Nzaramba; Douglas C. Scheuring; Anna L. Hale; Lavanya Reddivari; J. Creighton Miller (American Journal of Potato Research, 2010)

TX1523-1Ru/Y a.k.a Sierra Gold™: An early maturing, yellow-fleshed ruseet cultivar for the specialty/gourmet market - J. Creighton Miller; Douglas C. Scheuring; Jeffrey W. Koym; David G. Holm (American Journal of Potato Research, 2005)

Construction of BAC and BIBAC libraries and their applications for generation of SSR markers for genome analysis of chickpea, Cicer arietinum L. - J. Lichtenzveig; C. Scheuring; J. Dodge; S. Abbo; H.-B. Zhang (Theoretical and Applied Genetics, 2005)

Construction and characterization of a soybean bacterial artificial chromosome library and use of multiple complementary libraries for genome physical mapping - C.-C. Wu; P. Nimmakayala; F. A. Santos; R. Springman; C. Scheuring; K. Meksem; D. A. Lightfoot; H.-B. Zhang (Theoretical and Applied Genetics, 2004)

Molecular Analyses of Possible Mechanisms Coding for Low-Level Mupirocin Resistance in Clinical Staphylococcus aureus Isolates - F.-J. Schmitz; A. C. Fluit; E. Lindenlauf; S. Scheuring; K. Köhrer (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Selection, evaluation, and identification of improved Russet Norkotah strains - J. Creighton Miller; Douglas C. Scheuring; Jeannie P. Miller; George C. J. Fernandez (American Journal of Potato Research, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Untersuchungen zur Stoffwechselphysiologie des «Abwasserpilzes»Fusarium aquaeductuum Lagh - L. Scheuring; C. Zehender (Aquatic Sciences, 1962)